Water and development - Souza, Arun De (New Delhi, 2010)
This book shows how watershed development projects intervene in peoples lives and the ways in which an entire community gets reconstructed around the implementation of a new resource. It challenges the popular view that rural communities are an unchanging entity, steeped in tradition and economically stagnant. The author deconstructs these preconceived notions through which rural India is perceived and establishes how a community, far from being static and autonomous, is fluid and changing. In analysing the processes involved in bringing together a heterogeneous group of people for a common cause, the study raises pertinent questions is the mere fact of scarcity enough to motivate them to come together? Can scarcity enable them to put aside their differences and invent a new method to conserve and manage their available water? Explaining the dynamics engaged in it, the author focuses on: The way narrating a myth helps build a community, creates a utopian space of united action and solidarity one that transcends class-caste-factional divisions. The everyday political practices of the village and its relationship to the wider polity of the village and the state where factionalism is not just a divisive factor but also builds and sustains complex relationships. The image that a community portrays to outsiders who visit the village where all forms of contestations and plural interpretations are swept aside to present themselves as a distinct group with a sense of a we feeling. The village community is, thus, forged in a relationship with the present and lives in continuity with its past. It is intricately linked to the larger processes (both global and local) beyond its boundaries be it the global green movement, the changing aid policies, or the states present efforts to encourage NGOs to work with the government. It will also be of interest to policymakers, activists, NGOs and development practitioners.
Keywords: Watershed development-India